The importance of the Dead Sea Scrolls for the study of the explicit quotations in Ad Hebraeos - Steyn, Gert J. (HTS teologiese studies, 2016)
The important contribution that the Dead Sea Scrolls (DSS) hold for New Testament studies is probably most evident in Ad Hebraeos. This contribution seeks to present an overview of relevant extant DSS fragments available for an investigation of the Old Testament explicit quotations and motifs in the book of Hebrews. A large number of the explicit quotations in Hebrews were already alluded to, or even quoted, in some of the DSS. The DSS are of great importance for the study of the explicit quotations in Ad Hebraeos in at least four areas, namely in terms of its text-critical value, the hermeneutical methods employed in both the DSS and Hebrews, theological themes and motifs that surface in both works, and the socio-religious background in which these quotations are embedded. After these four areas are briefly explored, this contribution concludes, among others, that one can cautiously imagine a similar Jewish sectarian matrix from which certain Christian converts might have come – such as the author of Hebrews himself.